Cylindrical battery and electric device

CN122931079APending Publication Date: 2026-10-16CALB GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611224213.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-17
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]本发明的主要目的在于提供一种圆柱电池及用电设备,以解决现有技术中具有较高能量密度的圆柱电池常伴随着自放电严重的问题

Benefits of technology

[0008]By applying the technical solution of this invention, by simultaneously controlling the three key indicators—the radial dimension d of the core hole, the deformation resistance f of the negative electrode sheet in the direction perpendicular to its surface, and the puncture resistance q of the separator—to satisfy the relationship shown in equation (I), while ensuring a sufficiently high puncture resistance of the separator, the flexibility of the negative electrode sheet can be optimized to avoid powder shedding under bending conditions. This effectively reduces the positive and negative electrode micro-short circuits caused by electrode powder shedding, reduces the self-discharge rate of the cylindrical battery, and also takes into account good dynamic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The application provides a cylindrical battery and an electric device. The cylindrical battery comprises a winding core, the winding core comprises a positive electrode sheet, a diaphragm and a negative electrode sheet which are sequentially wound, the radial dimension of the winding core hole is d mm, the anti-deformation capacity of the negative electrode sheet in the direction perpendicular to the surface thereof is f mN, the puncture resistance of the diaphragm is q gf, and the three satisfy the relationship shown in formula (I): 2<=f*1000 / (d*q)<=88 (I). By simultaneously controlling the radial dimension d of the winding core hole, the anti-deformation capacity f of the negative electrode sheet in the direction perpendicular to the surface thereof and the puncture resistance q of the diaphragm to satisfy the relationship shown in formula (I), the flexibility of the negative electrode sheet can be optimized while ensuring a high puncture resistance of the diaphragm, the phenomenon of powder falling under bending conditions can be avoided, the positive-negative micro-short circuit caused by the powder falling of the electrode sheet can be effectively reduced, the self-discharge rate of the cylindrical battery is reduced, and good kinetic performance is considered.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of Chinese invention application filed on April 17, 2026, with application number CN2026105107281 and invention title "Cylindrical Battery and Electrical Device". Technical Field

[0002] This invention relates to the field of battery technology, and more specifically, to a cylindrical battery and an electrical device thereof. Background Technology

[0003] The structural characteristics of cylindrical batteries necessitate the use of electrodes under bending conditions. Furthermore, to improve the battery's volumetric energy density, the core holes typically need to be small. However, smaller core holes result in greater bending of the electrodes, making them more prone to microcracks during winding, especially in the high-curvature inner region, where localized delamination between the active material and the current collector may occur. These structural defects exacerbate stress concentration during cycling, causing crack propagation and ultimately leading to active material shedding (i.e., "powder shedding"). If this shed powder remains suspended in the electrolyte, it may deposit on the separator surface or form conductive pathways, triggering localized micro-short circuits and severe self-discharge.

[0004] Based on this, it is of great significance to research and develop a cylindrical battery that balances high energy density and low self-discharge rate. Summary of the Invention

[0005] The main objective of this invention is to provide a cylindrical battery and an electrical device to solve the problem that cylindrical batteries with high energy density in the prior art are often accompanied by severe self-discharge.

[0006] To achieve the above objectives, a first aspect of this application provides a cylindrical battery comprising a core, the core comprising a positive electrode, a separator, and a negative electrode wound sequentially, the radial dimension of the core hole being d mm, the negative electrode having a deformation resistance of f mN in a direction perpendicular to its surface, and the separator having a puncture resistance of q gf, the three satisfying the relationship shown in equation (I): 2≤f×1000 / (d×q)≤88 (I).

[0007] To achieve the above objectives, in a second aspect, this application provides an electrical device that includes the cylindrical battery described above.

[0008] By applying the technical solution of this invention, by simultaneously controlling the three key indicators—the radial dimension d of the core hole, the deformation resistance f of the negative electrode sheet in the direction perpendicular to its surface, and the puncture resistance q of the separator—to satisfy the relationship shown in equation (I), while ensuring a sufficiently high puncture resistance of the separator, the flexibility of the negative electrode sheet can be optimized to avoid powder shedding under bending conditions. This effectively reduces the positive and negative electrode micro-short circuits caused by electrode powder shedding, reduces the self-discharge rate of the cylindrical battery, and also takes into account good dynamic performance. Detailed Implementation

[0009] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the embodiments.

[0010] As described in the background section, existing cylindrical batteries suffer from the problem of simultaneously achieving excellent energy density and low self-discharge rate. To address this technical problem, a first aspect of this application provides a cylindrical battery comprising a core, the core including a positive electrode, a separator, and a negative electrode wound sequentially. The radial dimension of the core hole is d mm, the negative electrode's resistance to deformation in a direction perpendicular to its surface is f mN, and the separator's puncture resistance is q gf. These three properties satisfy the relationship shown in equation (I): 2 ≤ f × ​​1000 / (d × q) ≤ 88 (I).

[0011] In this application, the core refers to the wound cell, which is the main energy storage component of the battery. It refers to a cell made by winding a continuous positive electrode, negative electrode, and separator, with the separator located between adjacent positive and negative electrode sheets.

[0012] To improve the volumetric energy density of cylindrical batteries, the positive electrode, separator, and negative electrode need to be tightly wound. The smaller the core hole, the greater the bending stress on the electrode, causing active material to detach from the current collector (i.e., "material shedding"). These detached active material particles may be suspended in the electrolyte and migrate to the separator region with ion flow. If these particles deposit on the separator surface or embed in the microporous structure, they may bridge the positive and negative electrodes, forming micron-level conductive paths, causing localized electron conduction, i.e., "micro-short circuits," resulting in severe self-discharge and continuous energy consumption, leading to a decrease in the battery's storage capacity retention. In particular, the negative electrode material undergoes drastic volume changes during charge and discharge, making the risk of material shedding even greater.

[0013] In this application, on the one hand, by increasing the puncture resistance strength q of the separator, the integrity of the separator under mechanical stress is improved, effectively preventing the detached active material from penetrating the separator, blocking the conductive path formed between the positive and negative electrodes due to physical contact, avoiding micro-short circuits, and reducing the self-discharge rate of the cylindrical battery. However, when the puncture resistance strength q of the separator is too large, the excessive densification of the separator material structure or the excessive thickness of the coating restricts the migration channel of lithium ions, thereby increasing the DC internal resistance (DCR) of the battery and causing a decrease in the dynamic performance of the battery.

[0014] On the other hand, by reducing the negative electrode's resistance to deformation (f) in the direction perpendicular to its surface, the flexibility of the negative electrode is improved, allowing it to better adapt to deformation, reducing stress concentration, maintaining structural integrity, thereby reducing the risk of material loss, lowering the self-discharge rate of the cylindrical battery, and avoiding the problem of decreased cylindrical battery dynamics caused by excessively high puncture resistance (q) of the separator. If f is too low, the negative electrode structure will lack sufficient support, which may also affect the electrode integrity and interface stability, and adversely affect the battery's internal resistance (DCR).

[0015] Therefore, while controlling the core hole size d to increase energy density, the puncture resistance q of the separator and the deformation resistance f of the negative electrode sheet in the direction perpendicular to its surface are simultaneously adjusted and matched. When the relationship 2≤f×1000 / (d×q)≤88 (I) is satisfied, the self-discharge phenomenon of the battery can be alleviated and the dynamic performance of the battery can be improved.

[0016] For example, the value of f×1000 / (d×q) can be 2, 2.1, 3, 4, 4.5, 5.1, 6, 7, 7.9, 8, 9, 10, 11, 12.7, 13.1, 14, 15, 15.5, 16, 17, 18.4, 19, 20, 21, 21.6, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 35.4, 35.5, 36. The range of values ​​for one or any two of the following: 37, 38, 39, 40, 40.8, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 80, 81, 82, 83, 84, 85, 86, 87, 87.7, or 88.

[0017] By simultaneously controlling the three key indicators—the radial dimension d of the core hole, the deformation resistance f of the negative electrode sheet in the direction perpendicular to its surface, and the puncture resistance q of the separator—to satisfy the relationship shown in Equation (I), while ensuring a sufficiently high puncture resistance of the separator, the flexibility of the negative electrode sheet can be optimized to avoid powder shedding under bending conditions. This effectively reduces the positive and negative electrode micro-short circuits caused by electrode powder shedding, lowers the self-discharge rate of the cylindrical battery, and also ensures good dynamic performance.

[0018] In a preferred embodiment, the value of f×1000 / (d×q) ranges from 8 to 29. Compared to other ranges, limiting the value of f×1000 / (d×q) to the above range is beneficial to further avoid micro-short circuits between the positive and negative electrodes caused by electrode powder shedding, reduce the self-discharge rate of the battery, and take into account the dynamic performance.

[0019] In a preferred embodiment, 3mm ≤ d mm ≤ 10mm.

[0020] In a cylindrical battery, the core hole refers to the central through-hole formed during the winding process of the stacked positive electrode, separator, and negative electrode. Located on the central axis of the core, it serves as a channel for internal heat conduction and electrolyte flow. The radial dimension 'd' of the core hole in a cylindrical battery reflects the tightness of the winding of the stacked positive electrode, separator, and negative electrode. Tighter winding results in a smaller value for 'd', while looser winding results in a larger value for 'd'. To improve the volumetric energy density of the battery, a smaller core hole is generally required. However, a smaller core hole leads to greater bending of the electrode, increasing the risk of material loss and self-discharge, thus increasing the self-discharge rate of the cylindrical battery. Furthermore, a larger value for 'd' results in insufficient electrolyte wetting of the outer electrode layers, leading to increased local current density, concentration polarization, and a decrease in the kinetic performance of the cylindrical battery. Specifically, 'd mm' can be any value within the range of 3mm, 4mm, 5mm, 6mm, 7mm, 8mm, 9mm, and 10mm.

[0021] To further suppress the material shedding problem of cylindrical batteries, reduce the self-discharge rate of cylindrical batteries, and take into account the dynamic performance of batteries, preferably, 4mm≤d mm≤7mm.

[0022] It should be noted that the test method for the radial dimension d of the core hole in this application includes: using a CT device to obtain a top view of a cross section perpendicular to the height direction of the empty battery cell. This cross section clearly shows the boundary line of the core hole and the outer boundary line of the empty battery cell. Six points are selected on the boundary line of the core hole, of which the line connecting two points passes through the center point of the core hole. The distance between these two points is the diameter. The average value of three measurements is taken as the radial dimension d of the core hole.

[0023] In this application, the radial dimension of the core hole can be controlled by the diameter of the winding needle (3-10mm). The larger the diameter of the winding needle, the larger the radial dimension of the core hole.

[0024] In a preferred embodiment, 10mN ≤ f mN ≤ 70mN.

[0025] The deformation resistance *f* of a negative electrode sheet in the direction perpendicular to its surface is a performance indicator that measures its ability to maintain its original structure without deformation when subjected to external force. It reflects the flexibility of the negative electrode sheet, especially in cylindrical batteries where the negative electrode sheet is wound inside the cell, its flexibility is closely related to the degree of winding. It should be noted that in this application, the deformation resistance *f* of the negative electrode sheet in the direction perpendicular to its surface refers to the maximum stress generated during the deformation of the negative electrode sheet sample when the slit width in the microcomputer flexibility tester is 20 mm and the descent depth of the sheet probe is 8 mm. The larger the value of *f*, the worse the flexibility of the negative electrode sheet, making it difficult to wind. Furthermore, an overly hard and brittle negative electrode sheet may crack or break during processing, increasing the risk of material loss, causing severe micro-short circuits, and resulting in an increased self-discharge rate of the cylindrical battery. Specifically, f mN can be a range of one or any two of the following: 10mN, 15mN, 20mN, 25mN, 30mN, 35mN, 40mN, 45mN, 50mN, 55mN, 60mN, 65mN, and 70mN.

[0026] To further suppress material loss and micro-short circuits and reduce the self-discharge rate of cylindrical batteries, preferably, 25mN≤fmN≤55mN.

[0027] It should be noted that the test method for the negative electrode sheet's resistance to deformation f in the direction perpendicular to its surface in this application includes: discharging the cylindrical battery with 0.1C, disassembling it and removing the negative electrode sheet, cutting the outer electrode sheet into 5cm×5cm specifications, placing it in a constant temperature and humidity room with a temperature of 25±3℃ and a humidity of 35±3% for more than 1 hour, and then placing the electrode sheet on the platform of a microcomputer softness tester (Dongguan Internes Precision Instruments Co., Ltd., model ITM-RRD01), setting the gap width to 20mm and the descent depth of the sheet probe to 8mm, and measuring the negative electrode sheet's resistance to deformation f in the direction perpendicular to its surface.

[0028] In this application, the thickness ratio of the negative electrode current collector to the negative electrode material layer can be adjusted to 0.027 to 0.11 by adjusting the thickness of the negative electrode material layer to 50 to 200 μm. The smaller the ratio, the thicker the negative electrode material layer and the worse the flexibility.

[0029] The negative electrode material layer includes a rigid binder and a flexible binder. In this application, the flexibility of the negative electrode sheet can be controlled by adjusting the content of acrylic acid in the rigid binder (polyacrylic acid binder) and the content of butadiene in the flexible binder (styrene-butadiene rubber binder), as well as their mass ratio. A higher acrylic acid content in the polyacrylic acid binder results in greater rigidity; a higher butadiene content in the styrene-butadiene rubber binder results in greater flexibility. The mass ratio of the polyacrylic acid binder to the styrene-butadiene rubber binder is 0.4:2.6 to 2.3:0.7. A higher proportion of the styrene-butadiene rubber binder results in better flexibility of the negative electrode sheet and a smaller f-value. For example, the mass ratio of the polyacrylic acid binder to the styrene-butadiene rubber binder can be any one or both of the following: 0.4:2.6, 1:2, 1.4:1.6, 1:1, 1.6:1.4, 1.7:1.3, 1.8:1.2, 2:1, 2.3:0.7.

[0030] In a preferred embodiment, 220gf≤qgf≤620gf.

[0031] The puncture resistance q of a separator refers to its ability to resist mechanical damage during battery assembly and use, and it is crucial for preventing short circuits between the positive and negative electrodes inside the battery. In this application, the puncture resistance q of the separator refers to the maximum force detected when the separator sample is punctured by a spherical needle with a diameter of 1 mm and a tip radius of 0.5 mm. The smaller the value of q, the less mechanical strength the separator has, making it easier to be punctured, leading to direct contact between the positive and negative electrodes, causing a micro-short circuit, resulting in self-discharge, and thus increasing the self-discharge rate of the cylindrical battery. If the value of q is too large, the separator material structure is excessively dense or the coating is too thick, restricting the migration channels of lithium ions, resulting in poor kinetic performance of the cylindrical battery. Specifically, q gf can be a range of one or any two of the following: 220gf, 240gf, 260gf, 280gf, 300gf, 320gf, 340gf, 360gf, 380gf, 400gf, 420gf, 440gf, 460gf, 480gf, 500gf, 520gf, 540gf, 560gf, 580gf, 600gf, and 620gf.

[0032] To further improve lithium-ion transport efficiency while suppressing electrode powder shedding, avoiding micro-short circuits, reducing the self-discharge rate of cylindrical batteries, and taking into account dynamic performance, preferably, 420gf≤qgf≤530gf.

[0033] It should be noted that the test method for the puncture resistance strength q of the separator in this application includes: discharging the cylindrical battery to 0.33C, disassembling and removing the separator, soaking it in DMC solvent for 10 minutes, and removing the separator sample; cutting it into 100mm×100mm test samples; fixing the separator with a separator puncture fixture with an inner diameter of 50mm, using a spherical needle with a diameter of 1mm and a tip radius of 0.5mm, testing under a sensor condition of 500N, and testing under a puncture speed of 100mm / min, and recording the maximum force during the penetration process as the puncture resistance strength q of the separator.

[0034] In this field, coated separators are commonly used as battery separators. In a preferred embodiment, the separator includes a base film and a coating disposed on the surface of the base film. During the preparation of the separator, the puncture resistance q of the separator is controlled by adjusting the thickness of the separator (5.5–20 μm, with the coating thickness adjusted to 0.5–8 μm and the base film thickness to 5–12 μm, respectively) and the ratio of the coating thickness to the base film thickness (0.1–0.67). The thicker the separator and the larger the ratio of the coating thickness to the base film thickness, the larger q becomes.

[0035] In this application, the diameter of the core refers to the diameter (in mm) of the bare cell obtained after disassembling the cylindrical battery, excluding the thickness of the casing. In a preferred embodiment, the ratio of the radial dimension d of the core hole to the diameter of the core is 0.066 to 0.22. This ratio includes, but is not limited to, the range described above. Limiting it to this range helps prevent excessive bending stress on the electrode sheets due to tight winding, which can lead to powder shedding and thus suppress self-discharge, reducing the self-discharge rate of the cylindrical battery. Furthermore, it promotes sufficient electrolyte wetting, increases the lithium-ion transport rate, and improves the kinetic performance of the cylindrical battery.

[0036] In a preferred embodiment, the negative electrode sheet includes a negative electrode current collector and negative electrode material layers disposed on both sides of the negative electrode current collector. The negative electrode material layers include a negative electrode material, and the negative electrode material includes a negative electrode active material. The negative electrode sheet employing the above structure can improve the energy density of the cylindrical battery.

[0037] In a preferred embodiment, the ratio of the thickness of the negative electrode current collector to the thickness of the negative electrode material layer is 0.027 to 0.11. This ratio includes, but is not limited to, the range described above. Limiting it to this range helps to further utilize the electrochemical capacity of the negative electrode active material in the negative electrode material layer, thereby improving the energy density of the cylindrical battery. Simultaneously, it also helps to suppress the peeling of the negative electrode active material, reduce self-discharge, lower the self-discharge rate of the cylindrical battery, shorten the lithium-ion transport path, and improve the kinetic performance of the cylindrical battery.

[0038] In a preferred embodiment, the thickness of the negative electrode material layer is 50–200 μm. The thickness of the negative electrode material layer includes, but is not limited to, the above range. Limiting it to this range allows for a more suitable amount of active material loaded on the surface of the negative electrode current collector, which helps shorten the lithium-ion transport path, promotes efficient lithium-ion insertion / extraction within the negative electrode sheet, and improves the kinetic performance of the cylindrical battery. Furthermore, it helps suppress the peeling of the negative electrode active material and reduces the self-discharge rate of the cylindrical battery. Specifically, the thickness of the negative electrode material layer can be one or any two of the following: 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, and 200 μm.

[0039] It should be noted that the test method for the thickness of the negative electrode material layer in this application includes: discharging the cylindrical battery to 0.33C, disassembling the battery and taking out the negative electrode sheet, soaking the negative electrode sheet in DMC solvent for 10 minutes, measuring its thickness with a micrometer and recording it as h1, wiping the coating on the surface of the negative electrode sheet with water, and measuring the thickness of the negative electrode current collector h2. h1-h2 is the thickness of the negative electrode material layer.

[0040] In a preferred embodiment, the thickness of the negative electrode current collector is 4–7 μm. The thickness of the negative electrode current collector includes, but is not limited to, the above range. Limiting it to this range helps reduce the "ineffective volume" and "dead weight" inside the battery, leaving more space for the negative electrode active material or electrolyte within the same volume. This facilitates increasing the loading of the negative electrode active material or improving electrolyte distribution, indirectly enhancing ion migration efficiency and improving the battery's kinetic performance. It also provides stronger mechanical support and interfacial bonding stability, effectively resisting stress shocks during manufacturing and cycling, reducing the risk of active material shedding, and thus maximizing its electrochemical capacity, thereby reducing the self-discharge rate of the cylindrical battery. Specifically, the thickness of the negative electrode current collector can be one or any combination of 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, and 7 μm.

[0041] In a preferred embodiment, the Dv50 of the negative electrode material is 5–15 μm. Compared to other ranges, limiting the Dv50 of the negative electrode material layer to this range is beneficial for better adapting to mechanical stress during the manufacturing and use of the cylindrical battery, reducing cracking and shedding of the active material, lowering the self-discharge rate of the cylindrical battery, and shortening the diffusion path of lithium ions in the negative electrode sheet, thereby improving the kinetic performance of the cylindrical battery. Specifically, the Dv50 of the negative electrode material layer can be one or any two of the following: 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, and 15 μm.

[0042] In a preferred embodiment, the negative electrode active material includes, but is not limited to, graphite and / or silicon-based materials. Using the above-mentioned types of negative electrode active materials is beneficial for improving the kinetic performance of cylindrical batteries and reducing their self-discharge rate.

[0043] In a preferred embodiment, the negative electrode active material is graphite, and 15 ≤ f ≤ 45 mN. Graphite has a layered structure, allowing lithium ions to reversibly insert / extract between layers with a volume change of only about 10% to 12%. The structure is not easily broken. When graphite is used as the negative electrode active material, limiting the deformation resistance f of the negative electrode sheet within the above range helps to suppress the occurrence of electrode powder shedding, thereby suppressing self-discharge and reducing the self-discharge rate of the cylindrical battery.

[0044] In another preferred embodiment, the negative electrode active material is a silicon-based material, and 25 ≤ f ≤ 55 mN. Silicon-based materials are beneficial for improving the energy density of the battery, but compared to graphite, they expand more easily during charging and discharging, leading to a greater likelihood of silicon-based materials shedding powder. When using silicon-based materials as the negative electrode active material, limiting the deformation resistance f of the negative electrode sheet within the aforementioned range helps to suppress the occurrence of electrode sheet powder shedding, thereby suppressing micro-short circuits between the positive and negative electrodes and reducing the self-discharge rate of the cylindrical battery.

[0045] In a preferred embodiment, the negative electrode active material is a silicon-based material, and the mass percentage of silicon in the negative electrode material layer is 1–15 wt%. The silicon content in the negative electrode material layer includes, but is not limited to, the above range. Limiting it within this range helps to suppress electrode powder shedding, thereby suppressing micro-short circuits between the positive and negative electrodes, and thus reducing the self-discharge rate of the cylindrical battery. Specifically, the mass percentage of silicon can be any combination of 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, and 15 wt%.

[0046] It should be noted that the test method for the mass percentage content of silicon (Si) element in the negative electrode material layer in this application includes: (1) Pretreatment: the battery is discharged to 2.5V at 0.33C, the electrode sheet of the lithium-ion battery in the empty state is taken and soaked in dimethyl carbonate (DMC) solution at room temperature for 4h. After soaking, the electrode sheet is taken out and dried in a vacuum environment. The active material powder on the surface of the electrode sheet is scraped off with a ceramic knife; (2) the silicon content in the negative electrode sheet is tested by alkaline dissolution-ICP method. The negative electrode material layer powder after scraping is weighed, placed in a nickel crucible pre-filled with potassium hydroxide, and a small amount of potassium hydroxide is added to cover the sample surface. Two drops of ethanol are added, and the sample is heated on an electric furnace until the potassium hydroxide melts and dehydrates. Then it is transferred to a muffle furnace at 1100℃, kept in a molten state, and kept at a temperature for 8h. The nickel crucible is taken out and cooled slightly. The sample is placed in a 300m In a L-shaped plastic beaker, hot water was added for extraction. After the reaction, the crucible was washed out. HCl was added to the extract for acidification, and hydrogen peroxide and hydrochloric acid were added to form a mixed acid to ensure a more thorough conversion of silicon compounds to silicon ions. After cooling, the extract was washed out with water and transferred to a 100 mL volumetric flask. The volume was adjusted to a final volume, and the solution was shaken well. After standing, a portion of the solution was transferred to another 100 mL volumetric flask, adjusted to a final volume, shaken well, and allowed to stand until clear to obtain the test solution. A blank solution was prepared as a control; no powder was added to the blank solution. Following the operating procedure, a blank sample control was prepared to eliminate any potential influences during the operation. ICP testing was performed on the test solution. Experimental conditions were set as follows: based on the characteristics of the sample and the ICP testing of the test solution, the detection wavelength for Si was selected as 288.158 nm. The mass percentage of Si was determined by ICP testing.

[0047] In the preparation of negative electrode sheets, a slurry containing negative electrode active material is typically coated onto the surface of the negative electrode current collector. In a preferred embodiment, the compacted density of the negative electrode sheet is 1.25–1.6 g / cm³. 3 Compared to other ranges, limiting the compaction density of the negative electrode sheet within the aforementioned range facilitates thorough wetting of the negative electrode sheet by the electrolyte, optimizes the lithium-ion insertion / extraction path, improves the kinetic performance of the cylindrical battery, and simultaneously allows for tighter contact between active material particles and between particles and the current collector, reducing porosity. This improves the overall mechanical strength and structural stability of the electrode, suppresses the volume expansion effect of the active material during charge and discharge, reduces the risk of negative electrode sheet shedding, and reduces micro-short circuits between the positive and negative electrodes, thereby helping to reduce the self-discharge rate of the cylindrical battery. Specifically, the compaction density of the negative electrode sheet can be 1.25 g / cm³. 3 1.3g / cm 3 1.35g / cm 3 1.4g / cm 3 1.45g / cm 3 1.5g / cm 3 1.55g / cm3 1.6g / cm 3 The range of one or any two of them.

[0048] In a preferred embodiment, the thickness of the separator is 5.5–20 μm. The separator thickness includes, but is not limited to, the above range. Limiting it within this range helps shorten the lithium-ion transport path and allows powder from the electrode to easily pass through the separator, achieving a better balance between the separator's mechanical strength and electrochemical performance. This, in turn, helps reduce the self-discharge rate of the cylindrical battery while maintaining good kinetic performance. Specifically, the separator thickness can be one or any two of the following: 5.5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, and 20 μm.

[0049] It should be noted that the test method for the membrane thickness in this application includes: discharging the cylindrical battery to 0.33C, disassembling and removing the membrane, soaking it in DMC solvent for 30 minutes, drying it, and then measuring the membrane thickness with a micrometer.

[0050] In a preferred embodiment, the permeability of the separator is 190–380 s / 100 mL. Compared to other ranges, limiting the permeability of the separator to this range is beneficial for adsorbing more electrolyte, providing more microscopic channels for lithium ions to pass through, reducing the resistance to lithium ion migration, thereby improving the kinetic performance of the battery. At the same time, it is also beneficial for improving the mechanical strength of the separator. The denser the separator structure, the more effectively it can block the penetration of burrs, dust or lithium dendrites on the electrode surface, avoiding the formation of local conductive paths, thereby helping to reduce the self-discharge rate of the cylindrical battery while taking into account the kinetic performance. Specifically, the air permeability of the diaphragm can be one or any two of the following values: 190s / 100mL, 200s / 100mL, 210s / 100mL, 220s / 100mL, 230s / 100mL, 240s / 100mL, 250s / 100mL, 260s / 100mL, 270s / 100mL, 280s / 100mL, 290s / 100mL, 300s / 100mL, 310s / 100mL, 320s / 100mL, 330s / 100mL, 340s / 100mL, 350s / 100mL, 360s / 100mL, 370s / 100mL, and 380s / 100mL.

[0051] The air permeability of a membrane is related to its material, composition, and micropore structure. The air permeability of a membrane can be changed by adjusting the type of base membrane, the type of coating material, and the areal density of the coating.

[0052] It should be noted that the air permeability of the diaphragm in this application was measured using the following method: discharging the battery to 2.5V at 0.33C, removing the empty battery, disassembling and taking out the diaphragm, immersing it in DMC solvent for 10 minutes to obtain a diaphragm sample; using a diaphragm air permeability meter, in an environment with relative humidity <2%RH and 101.3KPa±5KPa, the instrument applied a pressure of 1.21KPa, and the measured area through which 100mL of air passed was 6.45cm². 2 Time for diaphragm samples.

[0053] In a preferred embodiment, the coating material disposed on the surface of the base film includes, but is not limited to, one or more of SiO2, TiO2, Al2O3, aramid, polyvinylidene fluoride, polyimide, polyacrylonitrile, and polyethylene terephthalate. Among these, SiO2, TiO2, Al2O3, and aramid can significantly improve the puncture resistance of the separator, while polyvinylidene fluoride, polyimide, polyacrylonitrile, and polyethylene terephthalate are used in combination with SiO2, TiO2, and Al2O3. Compared to other types, using the above-mentioned coating materials is beneficial for improving lithium-ion transport efficiency and accelerating charge exchange; it also helps to reduce internal resistance, thereby improving the kinetic performance of the cylindrical battery and reducing its self-discharge rate.

[0054] In a preferred embodiment, the areal density of the coating is 0.5–10 g / cm³. 2 The areal density of the coating includes, but is not limited to, the range described above. Limiting it within this range not only helps resist external punctures but also helps alleviate local stress concentration, reduces the risk of micro-short circuits between the positive and negative electrodes, lowers the self-discharge rate of the cylindrical battery, and facilitates sufficient electrolyte wetting of the separator, promoting lithium-ion transport within the separator and improving the kinetic performance of the cylindrical battery. Specifically, the areal density of the coating can be 0.5 g / cm³. 2 0.6g / cm 2 0.7g / cm 2 0.8g / cm 2 0.9g / cm 2 1.0g / cm 2 2.0g / cm 2 3.0g / cm 2 4.0g / cm 2 5.0g / cm 2 6.0g / cm 2 7.0g / cm 2 8.0g / cm 2 9.0g / cm 2 10g / cm 2 The range of one or any two of them.

[0055] In a preferred embodiment, the base membrane material includes, but is not limited to, polyethylene and / or aramid polymers. Compared to other types, using the above-mentioned types of base membranes is beneficial to improving the puncture resistance c of the separator, thereby helping to reduce the self-discharge rate of the cylindrical battery.

[0056] In a preferred embodiment, the positive electrode sheet includes a positive current collector and a positive electrode material layer disposed on both sides of the positive current collector. The positive electrode material layer includes a positive electrode material, which includes a positive electrode active material. The positive electrode sheet with the above structure facilitates more uniform stress distribution during rolling, reduces the risk of material loss due to localized stretching or internal stress concentration, and lowers the self-discharge rate of the cylindrical battery.

[0057] In a preferred embodiment, the compaction density of the positive electrode sheet is 3.4–3.7 g / cm³. 3 The compaction density of the positive electrode sheet includes, but is not limited to, the range mentioned above. Limiting it to this range is beneficial for the electrolyte to fully wet the positive electrode sheet, optimize the lithium-ion insertion / extraction path, improve the dynamic performance of the cylindrical battery, and avoid excessive compaction density, which could cause the positive electrode material to break and lead to material loss, and reduce the self-discharge rate of the cylindrical battery.

[0058] In a preferred embodiment, the method for preparing the positive electrode sheet includes mixing a positive electrode active material, a positive electrode conductive agent, a positive electrode binder and an optional first dispersant, adding a first solvent to obtain a positive electrode slurry, wherein the mass percentage of the positive electrode active material, the positive electrode conductive agent, the positive electrode binder and the first dispersant is (90-99%):(0.5-5%):(0.5-5%):(0-2%); coating the positive electrode slurry on both sides of the positive electrode current collector, drying, rolling and slitting to obtain the positive electrode sheet.

[0059] In a preferred embodiment, the positive electrode active material includes, but is not limited to, nickel-cobalt ternary materials, and the mass percentage of nickel in the positive electrode material is 80-95 wt%. The mass percentage of nickel in the positive electrode material includes, but is not limited to, the above range, and limiting it within this range is beneficial for improving the energy density of the cylindrical battery. Specifically, the mass percentage of nickel in the positive electrode material can be one or any two of the following: 80 wt%, 82 wt%, 84 wt%, 86 wt%, 88 wt%, 90 wt%, 92 wt%, 94 wt%, and 95 wt%.

[0060] Nickel is the main electrochemically active element in ternary materials. The higher its content, the more electrons participate in redox reactions, and the higher the specific capacity of the material. However, as the nickel content increases, the positive electrode active material undergoes a slow oxidative decomposition reaction, and the particle surface undergoes a "reconstruction" phenomenon: the originally ordered layered structure (R-3m) gradually transforms into a disordered rock salt phase or spinel phase. This new phase does not have the ability to insert or extract lithium ions, resulting in a decrease in the kinetic performance of cylindrical batteries.

[0061] In a preferred embodiment, the nickel-cobalt ternary material satisfies the general formula. Wherein, 0.75≤x≤1.2, 0<y<1; 0<z<1, 0<m<1, y+z+m=1; 0≤n≤0.2, 1≤h≤2.5, 0≤g≤1, h+g≤3; M1 can be Mn and / or Al, M2 includes but is not limited to at least one of B, Zr, Ti, Si, Mo, La, Ce, Te, Nb, Ta, Si, Al, W, Sr, V, Y, Mg, Co, and Li, and R includes but is not limited to at least one of N, F, S, and Cl.

[0062] Positive conductive agents include, but are not limited to, at least one of superconducting carbon (SP), acetylene black, carbon black, Ketjen black, nanotubes (CNT), graphene, and carbon nanofibers.

[0063] The positive electrode binder includes, but is not limited to, at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0064] The first dispersant includes, but is not limited to, at least one of the following: acrylic acid, acrylate, polyether ester, phosphate ester, small molecule alkanolamine, polyurethane, modified styrene / maleic anhydride, hydrogenated nitrile butadiene rubber (HNBR), polyvinylpyrrolidone (PVP), and polyethylene glycol (PEG).

[0065] The positive current collector can be a metal foil or a composite current collector.

[0066] Specifically, the metal foil can be aluminum or an aluminum alloy.

[0067] Specifically, the composite current collector includes a middle high-density layer and metal layers disposed on both sides of the polymer layer. The polymer layer includes polymer materials, including at least one of polyamide (PA), polyterephthalate, polyimide (PI), polyethylene (PE), polypropylene (PP), polystyrene (PPE), polyvinyl chloride (PVC), aramid, acrylonitrile-butadiene-styrene copolymer (ABS), polybutylene terephthalate (PET), poly(p-phenylene terephthalamide) (PPTA), polypropylene (PPE), polyoxymethylene (POM), epoxy resin, phenolic resin, polytetrafluoroethylene (PTEE), polyvinylidene fluoride (PVDF), silicone rubber, polycarbonate (PC), polyvinyl alcohol (PVA), polyethylene glycol (PEG), cellulose, starch, protein, their derivatives, their crosslinks, and their copolymers. The metal layer may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy.

[0068] The first solvent includes, but is not limited to, N-methylpyrrolidone (NMP).

[0069] In a preferred embodiment, the method for preparing the negative electrode sheet includes: mixing a negative electrode active material, a negative electrode conductive agent, a negative electrode binder and a second dispersant, adding a second solvent to obtain a negative electrode slurry, wherein the mass percentage of the negative electrode active material, the negative electrode conductive agent, the negative electrode binder and the second dispersant is (90-98):(0.6-5):(1.5-5):(0.3-1.5), coating the negative electrode slurry on both sides of the negative electrode current collector, drying, rolling and slitting to obtain the negative electrode sheet.

[0070] The negative electrode conductive agent includes, but is not limited to, one or more of superconducting carbon (SP), conductive graphite, acetylene black, carbon black, Ketjen black, carbon nanotubes (CNT), graphene, and carbon nanofibers.

[0071] The negative electrode binder includes, but is not limited to, at least one of styrene-butadiene rubber (SBR), waterborne acrylic resin, sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and sodium carboxymethyl cellulose (CMC). Among these, styrene-butadiene rubber (SBR) is a flexible binder. The waterborne acrylic resin can be polyacrylic acid (PAA) or polymethacrylic acid (PMAA).

[0072] The second dispersant includes, but is not limited to, at least one of acrylic acid, acrylate, polyether ester, phosphate ester, small molecule alkanolamine, polyurethane, modified styrene / maleic anhydride, hydrogenated nitrile butadiene rubber (HNBR), and polyvinylpyrrolidone (PVP).

[0073] Negative current collectors include, but are not limited to, metal foil or composite current collectors.

[0074] Specifically, the metal foil can be copper or a copper alloy.

[0075] Specifically, the composite current collector includes an intermediate polymer layer and metal layers disposed on both sides of the polymer layer. The polymer layer includes polymer materials, which include at least one of the following: polyamide (PA), polyterephthalate, polyimide (PI), polyethylene (PE), polypropylene (PP), polystyrene (PPE), polyvinyl chloride (PVC), aramid, acrylonitrile-butadiene-styrene copolymer (ABS), polybutylene terephthalate (PET), poly(p-phenylene terephthalamide) (PPTA), polypropylene (PPE), polyoxymethylene (POM), epoxy resin, phenolic resin, polytetrafluoroethylene (PTEE), polyvinylidene fluoride (PVDF), silicone rubber, polycarbonate (PC), polyvinyl alcohol (PVA), polyethylene glycol (PEG), cellulose, starch, protein, their derivatives, their crosslinks, and their copolymers.

[0076] The metal layer includes, but is not limited to, at least one of copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys.

[0077] The second solvent includes, but is not limited to, water.

[0078] In a preferred embodiment, the electrolyte comprises a lithium salt, a third solvent, and an additive.

[0079] Lithium salts include, but are not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP).

[0080] The lithium salt concentration in the electrolyte is 0.5–2.5 mol / L.

[0081] The third solvent includes, but is not limited to, at least one of the following: ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone, acetonitrile, dimethyl glycol ether (DME), dimethyl propylene glycol ether (PGME), and tetrahydrofuran.

[0082] Additives in the electrolyte can be negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery performance, such as additives that improve battery overcharge performance, battery high-temperature performance, and battery low-temperature performance.

[0083] Specifically, the positive electrode film-forming additives include, but are not limited to, at least one of anisole derivatives, polymeric monomers (such as xylene, phenylcyclohexane), and boron / nitrogen heterocyclic compounds (such as LiBOB); the negative electrode film-forming additives include, but are not limited to, at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), 1,3-propanesulfonate lactone (1,3-PS), vinyl sulfite (ES), and vinyl sulfate (DTD).

[0084] In a preferred embodiment, the positive electrode, separator, and negative electrode are stacked in sequence and wound to obtain a bare cell. The bare cell is placed in an outer packaging shell, dried, injected with electrolyte, and then packaged, left to stand, formed, and capacitated to obtain a cylindrical battery. The radial dimension of the winding needle during winding is d', the radial dimension of the core hole in the cylindrical battery is d, the deformation resistance of the negative electrode in the direction perpendicular to its surface is f, the puncture resistance of the separator is q, d' is the same as d, and d, f, and q have the same definitions as those described above.

[0085] In a second aspect, this application provides an electrical device comprising the cylindrical battery described above. The cylindrical battery provided above possesses both high energy density and low self-discharge. Applying this cylindrical battery to electrical devices (such as energy storage devices, electric ships, aircraft, laptops, power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and many other technological fields) can improve their overall performance and market competitiveness.

[0086] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.

[0087] Example 1

[0088] A method for preparing a cylindrical battery, comprising:

[0089] (1) Preparation of positive electrode sheet: The positive electrode active materials lithium nickel cobalt manganese oxide (NCM811), PVDF and CNT were mixed and uniformly dispersed in NMP at a weight ratio of 98.25:1:0.75 to obtain a positive electrode slurry; the positive electrode slurry was coated on both sides of an aluminum foil with a thickness of 12 μm to obtain a double-sided coated positive electrode sheet; then it was rolled under a pressure of 75 Torr and a temperature of 25℃, and cut to obtain a positive electrode sheet; the areal density of the positive electrode material layer was measured to be 380 g / m³. 2 The compaction density of the positive electrode is 3.55 g / cm³. 3 ;

[0090] (2) Preparation of negative electrode sheet: Graphite, silicon carbide, superconducting carbon (SP), rigid binder PAA (60% acrylic acid content), flexible binder SBR (80% butadiene content), and CMC were weighed and mixed in a weight ratio of 85.5:11.3:1:1:1:0.2, and deionized water was added to obtain a negative electrode slurry. The negative electrode slurry was coated on both sides of a copper foil with a thickness of 5.5 μm to obtain a double-sided coated negative electrode sheet. After rolling and cutting, the negative electrode sheet was obtained. The thickness of the negative electrode material layer was measured to be 74.5 μm, and the compaction density of the negative electrode sheet was 1.55 g / cm³. 3 The silicon content in the negative electrode material layer is 4.5 wt%.

[0091] (3) Preparation of electrolyte: EC, EMC and DEC are mixed in a volume ratio of 1:1:1 to obtain an organic solvent; fully dried lithium salt LiPF6 is dissolved in the above organic solvent, and 2wt% film-forming additive FEC is added to prepare an electrolyte of 1mol / L LiPF6 for later use.

[0092] (4) Separator: The structure of the separator is represented as: PVDF / Al2O3 / PE / Al2O3 / PVDF, wherein the thickness of PE is 10μm, the thickness of Al2O3 is 2μm, and the thickness of PVDF is 0.5μm.

[0093] (5) Battery assembly and formation: The positive electrode sheet obtained in step (1), the separator in step (4), and the negative electrode sheet obtained in step (2) are stacked in sequence, with the separator positioned between the positive and negative electrode sheets. The separator is then wound on a winding needle with a radial dimension of 6.5 mm to obtain a bare cell. The bare cell is placed in an outer packaging shell, dried, and then injected with electrolyte. After vacuum sealing, settling, formation, and shaping, a cylindrical battery is obtained. The specifications of this cylindrical battery are cylindrical type 4695, that is, its diameter is 46 mm and its height is 95 mm.

[0094] The self-discharge rate (k) and DCR (direct current resistance) of the cylindrical battery prepared in this application were tested.

[0095] The self-discharge rate test method in this application includes: discharging the lithium-ion battery at a constant current of 0.33C to 2.5V at 25℃, letting it stand for 10 minutes, charging it at a constant current to 4.25V, charging it at a constant voltage to 0.05C to cut off charging, and letting it stand for 10 minutes; repeating the above steps for a total of 3 charge-discharge cycles, using the third discharge capacity as the battery capacity, and then discharging it at a constant current of 0.33C to 30% SOC based on the actual rated capacity, letting it stand at 45℃ for 48 hours, then transferring it to a 25℃ environment and letting it stand for 12 hours, recording the voltage value as OCV1, and continuing to place it in a 25℃ environment for 48 hours and recording the voltage value as OCV2. Where H is the total settling time, i.e., 108h; the units of OCV1 and OCV2 are both mV.

[0096] The DCR (Direct Current Resistance) test method in this application includes: discharging a lithium-ion battery at a constant current of 0.33C to 2.5V at 25℃, letting it stand for 10 minutes, charging it at a constant current to 4.25V, charging it at a constant voltage to 0.05C (charging cutoff), and letting it stand for 10 minutes; repeating the above steps for a total of 3 discharges, and taking the capacity of the 3rd discharge as the battery capacity. Subsequently, based on the actual rated capacity, charging it at a constant current of 0.33C to 4.25V, charging it at a constant voltage to 0.05C (charging cutoff), letting it stand for 10 minutes, discharging it at a constant current of 0.33C to 30% SOC, letting it stand for 2 hours, recording the voltage V1, and then discharging it at 3C for 10 seconds, recording the voltage as V2 and the current as I, and calculating the DCR using the following formula: Where V1 and V2 are in mV, I is in A, and DCR is in mΩ.

[0097] In all embodiments and comparative examples of this application, the radial dimension d of the core hole, the deformation resistance f of the negative electrode sheet in the direction perpendicular to its surface, the puncture resistance q of the separator, the index of the relationship f×1000 / (d×q), the diameter of the winding needle, the diameter of the core, the ratio of d to the diameter of the core, the ratio of the thickness of the negative electrode current collector to the thickness of the negative electrode material layer, the thickness of the negative electrode material layer, the mass content of acrylic acid in polyacrylic acid (PAA), the mass content of butadiene in styrene-butadiene rubber (SBR), the mass ratio of PAA to SBR, the separator composition, the base film thickness, the ratio of the coating thickness to the base film thickness, the separator thickness, the separator air permeability test results, and the self-discharge rate and DCR test results are shown in Tables 1, 2, 3, 4 and 5, respectively.

[0098] Table 1

[0099]

[0100] Table 2

[0101]

[0102] Table 3

[0103]

[0104] Table 4

[0105]

[0106] Table 5

[0107]

[0108] As can be seen from the above description, the embodiments of the present invention achieve the following technical effects:

[0109] In Examples 1-16, 2≤f×1000 / (d×q)≤88 indicates that the bending stress on the electrode is moderate, the flexibility of the negative electrode is moderate, which alleviates the phenomenon of electrode shedding, and the mechanical strength of the separator is moderate, making it less likely to be punctured by electrode shedding and cause micro-short circuits between the positive and negative electrodes. This can suppress self-discharge, allowing the cylindrical battery to achieve both excellent self-discharge rate and dynamic performance. The self-discharge rate k is in the range of 0.002 to 0.021, and the discharge DCR is in the range of 1.4 to 3 mΩ.

[0110] Comparing Examples 1-7 and Examples 8-16, it can be seen that when f×1000 / (d×q) meets the preferred range of 8-29, the self-discharge rate and discharge DCR of the cylindrical battery are lower. When the parameters d, f, and q in Examples 1-5 further meet the preferred range, the self-discharge rate and discharge DCR of the cylindrical battery are further reduced.

[0111] As can be seen from Comparative Examples 1 and 2, even if the radial dimension d of the core hole, the deformation resistance f of the negative electrode sheet in the direction perpendicular to its surface, and the puncture resistance q of the separator all meet the range, the performance of the cylindrical battery will deteriorate when the value of f×1000 / (d×q) exceeds the range of 2 to 88. When f×1000 / (d×q)>88, the self-discharge rate will increase, and when f×1000 / (d×q)<2, the discharge DCR will increase.

[0112] As can be seen from Comparative Examples 3 and 4, when the radial dimension d of the core hole, the deformation resistance f of the negative electrode sheet in the direction perpendicular to its surface, and the puncture resistance q of the separator all exceed the range, and the value of f×1000 / (d×q) also exceeds the range of 2 to 88, the performance of the cylindrical battery will further deteriorate.

[0113] As can be seen from all the embodiments of this application, by simultaneously controlling the three key indicators of the radial dimension d of the core hole, the deformation resistance f of the negative electrode sheet in the direction perpendicular to its surface, and the puncture resistance q of the separator to satisfy the relationship shown in equation (I), while ensuring a sufficiently high puncture resistance of the separator, the flexibility of the negative electrode sheet can be optimized, avoiding powder shedding under bending conditions. This can effectively reduce the positive and negative electrode micro-short circuits caused by electrode powder shedding, reduce the self-discharge rate of the cylindrical battery, and take into account good dynamic performance.

[0114] It should be noted that the terms "first," "second," etc., used in the specification and claims of this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such terms can be used interchangeably where appropriate so that the embodiments of this application described herein can be implemented, for example, in a sequence other than those described herein.

[0115] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A cylindrical battery, characterized in that, The cylindrical battery includes a core, which comprises a positive electrode, a separator, and a negative electrode wound sequentially. The radial dimension of the core hole is d mm. The negative electrode has a deformation resistance of f mN in the direction perpendicular to its surface. The puncture resistance of the separator is q gf. The three satisfy the relationship shown in equation (I): 2≤f×1000 / (d×q)≤88 (I), Among them, 4mm≤d mm≤7mm; 25mN≤f mN≤55mN; 420gf≤q gf≤530gf.

2. The cylindrical battery according to claim 1, characterized in that, The value range of f×1000 / (d×q) is 8 to 29.

3. The cylindrical battery according to claim 1, characterized in that, The ratio of the radial dimension d mm of the core hole to the diameter of the core is 0.066 to 0.

22.

4. The cylindrical battery according to claim 1, characterized in that, The negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on both sides of the negative electrode current collector. The negative electrode material layer includes a negative electrode material, which includes a negative electrode active substance. The ratio of the thickness of the negative electrode current collector to the thickness of the negative electrode material layer is 0.027 to 0.

11.

5. The cylindrical battery according to claim 4, characterized in that, The thickness of the negative electrode material layer is 50–200 μm.

6. The cylindrical battery according to claim 4, characterized in that, The negative electrode material layer includes a polyacrylic acid binder and a styrene-butadiene rubber binder; the mass ratio of the polyacrylic acid binder to the styrene-butadiene rubber binder is 0.4:2.6 to 2.3:0.

7.

7. The cylindrical battery according to claim 1, characterized in that, The diaphragm includes a base membrane and a coating disposed on the surface of the base membrane. The thickness of the coating is 0.5 to 8 μm, and the thickness of the base membrane is 5 to 12 μm.

8. The cylindrical battery according to claim 7, characterized in that, The ratio of the thickness of the coating to the thickness of the base film is 0.1 to 0.

67.

9. The cylindrical battery according to claim 4, characterized in that, The thickness of the negative electrode current collector is 4–7 μm.

10. The cylindrical battery according to claim 4, characterized in that, The Dv50 of the negative electrode material is 5–15 μm.

11. The cylindrical battery according to claim 4, characterized in that, The negative electrode active material is selected from graphite and / or silicon-based materials.

12. The cylindrical battery according to claim 4, characterized in that, The negative electrode active material is graphite, and 15≤f≤45mN.

13. The cylindrical battery according to claim 4, characterized in that, The negative electrode active material is a silicon-based material, and 25≤f≤55mN.

14. The cylindrical battery according to claim 13, characterized in that, The mass percentage of silicon in the negative electrode material layer is 1 to 15 wt%.

15. The cylindrical battery according to claim 14, characterized in that, The average particle size of the silicon-based material is 5–9 μm.

16. The cylindrical battery according to claim 1, characterized in that, The compaction density of the negative electrode sheet is 1.25–1.6 g / cm³. 3 .

17. The cylindrical battery according to claim 1, characterized in that, The thickness of the diaphragm is 5.5–20 μm.

18. The cylindrical battery according to claim 1, characterized in that, The air permeability of the diaphragm is 190–380 s / 100 mL.

19. The cylindrical battery according to claim 18, characterized in that, The diaphragm includes a base membrane and a coating disposed on the surface of the base membrane, wherein the thickness of the coating is in the ratio of the thickness of the base membrane to the thickness of the base membrane, which is 0.1 to 0.

83.

20. The cylindrical battery according to claim 19, characterized in that, The coating material is selected from one or more of SiO2, TiO2, Al2O3, aramid, polyvinylidene fluoride, polyimide, polyacrylonitrile, and polyethylene terephthalate; the areal density of the coating is 0.5–10 g / cm³. 2 .

21. The cylindrical battery according to claim 19, characterized in that, The base film is selected from at least one of polyethylene, polypropylene, polyimide, and aramid polymer.

22. The cylindrical battery according to claim 1, characterized in that, The positive electrode sheet includes a positive current collector and a positive electrode material layer disposed on both sides of the positive current collector. The positive electrode material layer includes a positive electrode material, and the positive electrode material includes a positive electrode active material.

23. The cylindrical battery according to claim 1, characterized in that, The positive electrode sheet includes a positive current collector and a positive electrode material layer disposed on both sides of the positive current collector. The positive electrode material layer includes a positive electrode material, which includes a positive electrode active material. The positive electrode active material is selected from nickel-cobalt ternary materials, and the nickel-cobalt ternary material satisfies the general formula... Wherein, 0.75≤x≤1.2, 0<y<1, 0<z<1, 0<m<1, y+z+m=1, 0≤n≤0.2, 1≤h≤2.5, 0≤g≤1, h+g≤3; M1 can be Mn and / or Al, M2 is selected from at least one of B, Zr, Ti, Si, Mo, La, Ce, Te, Nb, Ta, Si, Al, W, Sr, V, Y, Mg, Co, Li, and R is selected from at least one of N, F, S, Cl.

24. The cylindrical battery according to claim 22, characterized in that, The compaction density of the positive electrode sheet is 3.4–3.7 g / cm³. 3 .

25. The cylindrical battery according to claim 24, characterized in that, The positive electrode active material is selected from nickel-cobalt ternary materials, and the mass percentage of nickel in the positive electrode material is 80-95 wt%.

26. The cylindrical battery according to claim 1, characterized in that, The cylindrical battery also includes an electrolyte, wherein the lithium salt concentration in the electrolyte is 0.5–2.5 mol / L.

27. An electrical appliance, characterized in that, The electrical device includes the cylindrical battery according to any one of claims 1 to 26.